Assessing returns to research investments in rice varietal development: Evidence from the Philippines and Bangladesh - Dikitanan, Rowell; Pede, Valerien O.; Rejesus, Roderick; Bhandari, Humnath; Alam, Monirul; Andrade, Robert Santiago (Elsevier, 2022)
This study estimates economic returns to investments in rice varietal development in the Philippines and Bangladesh. The net returns to IRRI and national partners' investments remain strongly positive. However, the returns are decreasing at a faster rate in the Philippines (24%) than in Bangladesh (6%). IRRI and national partners should continue investing in rice R&D, especially to develop superior rice varieties.